Bilateral tears of the retinal pigment epithelium. Issue 8 (August 1988) - Norose, K; Tanino, T; Segawa, K
Abstract : This paper describes bilateral tears of the retinal pigment epithelium (RPE) which followed photocoagulation treatment of retinal pigment epithelial detachment (PED) in the right eye and which occurred spontaneously in the left eye. A 66-year-old Japanese male presented with PED approximately 4 X 6 disc diameters in size in his right eye, and one disc diameter in the left eye, both in the macular regions. The right PED was treated by placing a row of argon laser photocoagulation along the margin of the PED, with avoidance of the papillomacular bundle. Five days after treatment the PED enlarged peripherally beyond the coagulated site. Nineteen days later an RPE tear developed at the temporal edge of the detachment in the right eye. The remaining detached RPE retracted centrally, forming curled folds. About 40 days after the initial examination the patient complained of sudden reduction of vision in his left eye. At this time an enlargement of the PED was found in his left eye. One week after this examination a small RPE tear was found in the nasal border of the PED in the left eye. The tear in the left eye gradually developed centrally to the fovea.